Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Spatiotemporal patterns of ENSO‐precipitation relationships in the tropical Andes of southern Peru and Bolivia - Joseph A. Jonaitis; L. Baker Perry; Peter T. Soulé; Christopher Thaxton; Marcos F. Andrade‐Flores; Tania Ita Vargas; Laura Ticona (International Journal of Climatology, 2021)
Precipitation in the outer tropical Andes is highly seasonal, exhibits considerable interannual variability, and is vital for regulating freshwater availability, flooding, glacier mass balance, and droughts. The primary driver of interannual variability is El Niño Southern Oscillation (ENSO), with most investigations reporting that the El Niño (La Niña) results in negative (positive) precipitation anomalies across the region. Recent investigations, however, have identified substantial spatiotemporal differences in ENSO‐precipitation relationships. Motivated by the dissimilarity of these findings, this study examines a carefully selected data set (≥ 90% completeness) of ground‐based precipitation observations from 75 high‐elevation (≥ 2,500 m above sea level) meteorological stations in the tropical Andes of southern Peru and Bolivia for the period 1972–2016. Distinct groups of stations and associated variability in precipitation characteristics (e.g., total seasonal precipitation, wet season onset, and wet season length) are identified. Using no spatial constraints, the K‐Means algorithm optimally grouped stations into five easily identifiable groups. The groups farthest from the Amazon basin had significant negative (positive) precipitation anomalies ( p

Winter climate variability in the southern Appalachian Mountains, 1910–2017 - Montana A. Eck; L. Baker Perry; Peter T. Soulé; Johnathan W. Sugg; Douglas K. Miller (International Journal of Climatology, 2019)
Located in the mid‐latitudes and exhibiting the greatest topographic relief in the eastern United States, the southern Appalachian Mountains (SAM) contain some of the most diverse climatological environments in the United States. This diversity is most pronounced in the winter season when temperature and snowfall can vary drastically across the region. In this study, we identify long‐term trends and variation of temperature and snowfall in the SAM of the southeastern United States during climatological winter (DJF) from 1910 to 2017. Along with recognizing statistically significant climatic trends, we also identify the influence of several teleconnection patterns, namely the El Niño‐Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Pacific Decadal Oscillation (PDO) that further scientific understanding of how this region has remained a climatic anomaly. Results of this study indicate the SAM have experienced a statistically significant long‐term cooling trend since the early 20th century, with recent decades suggesting a reversal towards a warming pattern. Snowfall exhibited high interannual variability, with the 1960s and 1970s producing anomalously high amounts of snowfall. Several atmospheric forcing couplings are identified that align with anomalous conditions in the region. Most notably, negative temperature anomalies and higher snowfall amounts were frequently found during El Niño and negative NAO seasons, with the opposite being true during La Niña and positive NAO winters. The influence of these teleconnection patterns was spatially dependent, with lower elevations and eastern‐facing slopes being highly dependent on the phase of ENSO for snowfall, whereas higher elevations and western‐facing slopes were more reliant on the NAO. The identification of pattern couplings is critical to improving understanding of the anomalous climate of the SAM, enhancing seasonal forecasting, and predicting future climate change in the region.

Relationships between tropical cyclones and heavy rainfall in the Carolina region of the USA - Charles E. Konrad; L. Baker Perry (International Journal of Climatology, 2010)
A strong association exists between exceptionally heavy rainfall and the movement of tropical cyclones (i.e. tropical depressions, tropical storms, and hurricanes) across the Carolina region of the USA. There is much variability, however, in the precipitation totals associated with each tropical cyclone. This variability is at least partially tied to various interactions between mid‐latitude features and the moisture plume that is advected around the tropical cyclone. In the first part of this study, a 55‐year precipitation events climatology is constructed that quantifies the influence of tropical cyclones on precipitation events with varying return intervals. In particular, it shows that the majority of the heaviest precipitation events in the eastern three‐quarters of the region are associated with tropical cyclones. In the second part of this study, a synoptic climatology is developed that reveals the relationships between precipitation totals and various atmospheric variables. The variables include the speed of movement, size, and strength of the tropical system as well as the relative position and strength of various synoptic features surrounding the tropical system. These synoptic features include the location of fronts, regions of upper level divergence and areas of high water vapor contents in the atmosphere. A tree regression model is used to develop a classification that summarizes these multivariate relationships. Four classes of tropical cyclones are identified that effectively differentiate tropical cyclones that produce relatively light versus extraordinarily heavy rainfall. Copyright © 2009 Royal Meteorological Society

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific - C. S. BAKER; L. MEDRANO‐GONZALEZ; J. CALAMBOKIDIS; A. PERRY; F. PICHLER; H. ROSENBAUM; J. M. STRALEY; J. URBAN‐RAMIREZ; M. YAMAGUCHI; O. VON ZIEGESAR (Molecular Ecology, 1998)
The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of target sequences amplified by the polymerase chain reaction (PCR–RFLP). There was little evidence of heterogeneity in the frequencies of mtDNA haplotypes or actin intron alleles due to the year or sex composition of the sample. However, frequencies of four mtDNA haplotypes showed marked regional differences in their distributions (Φ ST = 0.277; P n = 205 individuals) while the two alleles showed significant, but less marked, regional differences (Φ ST = 0.033; P n = 400 chromosomes). An hierarchical analysis of variance in frequencies of haplotypes and alleles supported the grouping of six regions into a central and eastern stock with further partitioning of variance among regions within stocks for haplotypes but not for alleles. Based on available genetic and demographic evidence, the southeastern Alaska and central California feeding grounds were selected for additional analyses of nuclear differentiation using allelic variation at four microsatellite loci. All four loci showed significant differences in allele frequencies (overall F ST = 0.043; P n = 139 chromosomes per locus), indicating at least partial reproductive isolation between the two regions as well as the segregation of mtDNA lineages. Although the two feeding grounds were not panmictic for nuclear or mitochondrial loci, estimates of long‐term migration rates suggested that male‐mediated gene flow was several‐fold greater than female gene flow. These results include and extend the range and sample size of previously published work, providing additional evidence for the significance of genetic management units within oceanic populations of humpback whales.